![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
已知a+b+c=0,化简1/b²+c²-a² + 1/c²+a²-b² + 1/a²+b²-c²
1个回答
展开全部
a+b+c=0
a+b=-c平方
(a+b)^2=c^2
a^2+b^2-c^2=-2ab
同理
b^2+c^2-a^2=-2cb
a^2+c^2-b^2=-2ac
1/(b^2+c^2-a^2) + 1/(c^2+a^2-b^2) + 1/(a^2+b^2-c^2)
=-1/2ab-1/2bc-1/2ac
=-c/2abc-a/2abc-b/2abc
=-(a+b+c)/abc
=0
a+b=-c平方
(a+b)^2=c^2
a^2+b^2-c^2=-2ab
同理
b^2+c^2-a^2=-2cb
a^2+c^2-b^2=-2ac
1/(b^2+c^2-a^2) + 1/(c^2+a^2-b^2) + 1/(a^2+b^2-c^2)
=-1/2ab-1/2bc-1/2ac
=-c/2abc-a/2abc-b/2abc
=-(a+b+c)/abc
=0
追问
确定对?
追答
是
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询